Butch Cassidy and the Sundance Kid - Hill, George Roy, 1921-2002; Newman, Paul, 1925-2008.; Ross, Katharine, 1942-; Redford, Robert; Bacharach, Burt.; Monash, Paul, 1917-2003; Goldman, William, 1931-; Foreman, John.; Twentieth Century Fox Home Entertainment, Inc.; Fox Video (Firm) (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2000)
The story of likeable outlaws, and among the most successful-until their ingenious caper, a train robbery, backfires.
English track: Dolby digital 2.0 mono.
French track: Dolby digital 2.0 mono.
Originally released as a motion picture in 1969.
Special features: animated menus; 45 minute documentary; cast and crew intrerviews; audio commentary by George Roy Hill, Hal David, Robert Crawford and Conrad Hall; theartrical trailer.
With: 'The making of Butch Cassidy and the Sundance Kid' as narrated by director George Roy Hill, author William Goldman, actors Paul Newman and Robert Redford.
Director of photography, Conrad Hall ; executive producer Paul Monash ; art directors, Jack Martin Smith, Phillip Jefferies ; music composed and conducted by Burt Bacharach, written by William Goldman.
Keywords: Sundance Kid -- Drama; Cassidy, Butch, -- b. 1866 -- Drama; Outlaws -- United States -- Drama; Films for the hearing impaired; Feature films; Western films